Braj B. Kachru and Asian Englishes. Issue 1 (9th July 2019) - Bolton, Kingsley
Abstract: This article discusses the range and scope of Braj Kachru's interests in Indian English and Asian Englishes, which were crucial to the development of world Englishes as a whole. The article begins with a discussion of the WE paradigm shift and then proceeds to highlight Kachru's contribution to Asian Englishes before moving on to provide an account of the contemporary dynamics of Asian Englishes from a sociolinguistic perspective. In this context, it is important to note that the field of 'Asian Englishes' owes much of its origins and development to the pioneer intellectual work of Braj Kachru from the 1960s onwards.